Revisiting the pedogenic carbonate isotopes and paleoenvironmental interpretation of Kanapoi. Issue 140 (March 2020) - Quinn, Rhonda L.; Lepre, Christopher J.
Abstract: Reconstructed habitats of Australopithecus anamensis at Kanapoi by Wynn (2000) yielded evidence for both wooded and grassy environments. Wynn's study was based on stable isotopic (δ 13 CPC, δ 18 OPC ) analyses of a small sample of pedogenic nodules ( n  = 14) collected from paleosols spanning Kanapoi's stratigraphic interval. Whether this small sample size adequately characterized Kanapoi's vegetation or was the result of time averaging remains unclear. To address this uncertainty, we sampled Kanapoi paleosols at 39 locations (78 analyses) from laterally extensive units. Our data demonstrate that Kanapoi offered A. anamensis diverse habitats distributed in temporally discrete stratigraphic horizons. Habitat heterogeneity appears to have been a real aspect of Kanapoi paleoenvironments and not an artifact of Wynn's (2000) small sample size or time averaging. We suggest habitat heterogeneity was influenced by the location of Kanapoi at the confluence of fluvial, deltaic, and lacustrine depositional environments. We also compared Kanapoi's δ 13 CPC and δ 18 OPC values to those of other Pliocene hominin localities in eastern Africa dated to 4.5–3.7 Ma. Kanapoi's δ 18 OPC values are significantly higher than most sites, potentially reflecting regional variability in water source δ 18 O values and/or more arid climatic conditions. Kanapoi's δ 13 CPC values indicate significantly more woody cover than at all other sites except those in the Turkana Basin. Kanapoi provided A. anamensis with a wide range of C3 –C4 resources as the C4 biome spread across eastern Africa. [Wynn, J.G., 2000. Paleosols, stable carbon isotopes and paleoenvironmental interpretation of Kanapoi, Northern Kenya. J. Hum. Evol. 39, 411–432.]